(untitled) (Global Journal of Management and Business Research, 2013)
This paper qualitatively reviewed the interaction between sexual harassment and job involvement among female teaching staff in Pakistan. The intensive literature review on the topic, along with personal cultural experience induced this study to conclude that the featured variables have an inverse relation with each other, with reference to female teaching staff in Pakistan.